Eelgrass (Zostera marina) and its epiphytic bacteria facilitate the sinking of microplastics in the seawater. (1st January 2022) - Zhao, Lingchao; Ru, Shaoguo; He, Jianlong; Zhang, Zhenzhong; Song, Xiukai; Wang, Dong; Li, Xuan; Wang, Jun
Abstract: Marine microplastics have received considerable attention as a global environmental issue. However, despite the constant accumulation of microplastics in the ocean, their transport processes and mechanisms remain poorly understood. This study investigated microplastics in the sediments of seagrass meadows and nearby regions without seagrass along the Shandong coast and found that the sediment in the seagrass meadows was a sink for microplastics. Subsequently, we evaluated the influence of eelgrass ( Zostera marina ), a common coastal seagrass, on the sedimentation of suspended polystyrene microplastics. The results showed that 0.5, 1.0, and 2.0 g/L eelgrass leaves decreased the abundance of microplastics in seawater in a dose-dependent manner over a period of 3–48 h under shaking conditions at 120 rpm at 22 °C. After 48 h of shaking, microplastic abundances in the 0.5, 1.0, and 2.0 g/L eelgrass groups significantly decreased by 46.9%, 53.1%, and 88.4%, respectively. Microplastics can adhere to eelgrass leaves and form biofilms, which promoted the formation of white floc that traps the suspended microplastics, causing them to sink. Furthermore, two epiphytic bacteria ( Vibrio and Exiguobacterium ) isolated from the eelgrass leaves decreased the abundances of suspended microplastics by 95.7% and 94.5%, respectively, in 48 h by accelerating the formation of biofilms on the microplastics. Therefore, eelgrass and its epiphytic bacteria facilitated the sinking of microplastics and increased the accumulation of microplastics in the sediments of seagrass meadows in coastal regions. Highlights: Microplastic level in sediments of eelgrass was higher than that in nearby bare area. Eelgrass leaves decreased microplastic abundance in a dose-dependent manner. Eelgrass promoted the formation of white floc to trap and sink microplastics. Eelgrass accelerated the formation of biofilm on the surface of microplastics. Two epiphytic bacteria Vibrio and Exiguobacterium accelerated microplastic settlement.